A case study related to the improvement of working and rest hours of oil tanker deck officers. Issue 4 (18th May 2016) - Uğurlu, Özkan
Abstract : Navigation safety on coastal waters is an extremely important issue. Fatigue is an important factor threatening navigation safety. Considering that the vessel type is an oil tanker, such a threat is not posed only to the crew but also to the environment. Most of the tankers navigating coastal waters are in the small tanker category. Therefore, this study examined the working and resting hours of the deck officers in the oil tankers navigating coastal waters. The study utilized the ISF Watchkeeper 3 program for assessing and interpreting the working periods. The study reached the conclusion that the first and second officers in particular are working under unsuitable conditions. To improve the working conditions of the deck officers, effects of additional cargo officer on board was investigated. This study is in quality of recommendation. The study elucidated that the cargo officer practice determines the working and resting hours of deck officers, in the work on the oil tankers, and compliance with the related conventions.